1975
DOI: 10.1901/jaba.1975.8-157
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Community Psychology: Training a Community Board to Problem Solve1

Abstract: This study demonstrated the effect of training nine lower socio-economic adults participating as policy board members in a federally funded rural community project to make behaviorally defined statements to increase problem-solving behaviors in board meetings. A multiple-baseline design across subjects and skills was used to analyze the behavioral categories of: (1) stating the problem; (2) finding solutions to the problem, and (3) implementing the action to the solution. Problem-solving responses during board… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0
3

Year Published

1977
1977
1984
1984

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 11 publications
1
36
0
3
Order By: Relevance
“…Behavior analysts have become increasingly cognizant of the fact that a demonstration of experimental control over a clearly defined response may not be sufficient to ensure that a given treatment or program will be adopted for use in settings other than those devoted primarily to research. Accordingly, recent studies have attempted to establish "social validity", both for the selection of the behaviors targetted for change (Quilitch, 1975) and for the degree of change (Briscoe et al, 1975;Minkin, Braukmann, Minkin, Timbers, Timbers, Phillips, and Wolf, 1976), by asking potential consumers or knowledgeable referees subjectively to evaluate these aspects of the research. In addition, when cost-efficiency analyses are performed, potential consumers can then be asked to evaluate a program's behavior-change capabilities in light of its associated costs, as was done in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavior analysts have become increasingly cognizant of the fact that a demonstration of experimental control over a clearly defined response may not be sufficient to ensure that a given treatment or program will be adopted for use in settings other than those devoted primarily to research. Accordingly, recent studies have attempted to establish "social validity", both for the selection of the behaviors targetted for change (Quilitch, 1975) and for the degree of change (Briscoe et al, 1975;Minkin, Braukmann, Minkin, Timbers, Timbers, Phillips, and Wolf, 1976), by asking potential consumers or knowledgeable referees subjectively to evaluate these aspects of the research. In addition, when cost-efficiency analyses are performed, potential consumers can then be asked to evaluate a program's behavior-change capabilities in light of its associated costs, as was done in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in the area of behavioral community psychology (Briscoe, Hoffman, and Bailey, 1975) have emphasized the use of prompting and reinforcement procedures in ameliorating many problems found in the natural or unstructured environment, and these techniques seem applicable to the recruitment and maintenance of senior citizen participation in community programs. Turner and Vernon (1975) found that telephone prompts increased the number of therapy appointments that were kept at a community mental health center; Geller, Farris, and Post (1973) (Clark, Burgess, and Hendee, 1972), increasing the usage of public transportation (Everett, Hayward, and Meyers, 1974), and maintaining attendance at self-help meetings for welfare clients (Miller and Miller, 1970).…”
mentioning
confidence: 99%
“…One subspecialty area within applied behavior analysis that has concerned itself with the study of larger subject populations has been termed "behavioral community psychology" (Briscoe, Hoffman, & Bailey, 1975;Fawcett, Mathews, & Fletcher, 1980;Glenwick & Jason, 1980). The dissemination of existing technologies of behavior change to expanding spheres of influence as large as the community and evenutally to state and national levels would most plausibly proceed through demonstration and community levels of analysis prior to large-scale implementation.…”
mentioning
confidence: 99%
“…This prospect has been an impetus for a program of research whose scope, nature, and purpose are suggested by terms such as community behavior analysis (Greene, 1981) and behavioral community psychology (Briscoe, Hoffman, & Bailey, 1975). This research has introduced behavioral engineering to systems responsible for energy conservation (Winett, 1980), traffic safety (Greene, Bailey, & Barber, 1981;Van Houten & Nau, 1981), and health care (Reiss, Piotrowski, & Bailey, 1976 Although community behavior analysis seems promising, it has generally introduced no more change in these systems than necessary to produce specific changes in the behavior of its consumers.…”
mentioning
confidence: 99%